A rare form of pancreatic diabetes complicated by portal venous thrombosis: A 25-year follow-up - Cheikhrouhou, Nesrine; Barka, Ines; Ach, Koussay; Chaieb, Larbi (Indian Journal of Case Reports, 2016)
Fibrocalculous pancreatic diabetes (FCPD) is an uncommon type of diabetes mellitus, so called tropical diabetes, due to chronic calcific non-alcoholic pancreatitis. This type of diabetes is associated to several particularities based on glycemic control and the occurrence of degenerative and metabolic complications, in addition to chronic pancreatitis complications such us venous thrombosis. We report here a rare case of a young North-African patient with long standing FCPD followed for 25 years and complicated by portal venous thrombosis. This case presentation highlights how important is to suspect fibrocalculous pancreatic diabetes especially in the presence of chronic abdominal pain. The follow-up of such patients should be focused not only on the clinical and biological markers of diabetes, but also on pancreatitis complications.